2013
DOI: 10.1002/rnc.3088
|View full text |Cite
|
Sign up to set email alerts
|

Optimal controller location in wireless networked control systems

Abstract: SUMMARYThe control performance of wireless networked control systems (WNCS) has been shown to heavily depend on the packet delivery quality of both the sensor‐to‐controller and controller‐to‐actuator communications. Such quality relies on the relative distance between the wireless transmitter and receiver, which naturally raises the challenging problem of controller placement in WNCS for optimal control performance. In this paper, we investigate the optimal controller location (OCL) problem in WNCS based on li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…We can see that V N À2 has the same form as equation (18). Repeating the derivation from equations (18) to (23), the optimal control law of u l, N À2 can be obtained. And similarly for other steps of u l, k , 8k.…”
Section: Optimal Control Law Derivationmentioning
confidence: 87%
See 2 more Smart Citations
“…We can see that V N À2 has the same form as equation (18). Repeating the derivation from equations (18) to (23), the optimal control law of u l, N À2 can be obtained. And similarly for other steps of u l, k , 8k.…”
Section: Optimal Control Law Derivationmentioning
confidence: 87%
“…Here, we consider a general case that both network-induced delays and packet dropouts are taken into consideration, and all of them are assumed to be independent and stochastic, such that only their distributions are known. 4,5,18,19 For a given controller located at the lth node, the sensor-to-controller (S/C) delay t sc l , the controller-toactuator (C/A) delay t ca l , and the sensor-to-actuator (S/ A) delay t tot are given respectively as…”
Section: System Model and Problem Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal LQ Gaussian control problem is considered in [19] [20] with the signal estimation over lossy networks. In [21] [22], the necessary and sufficient conditions under which the closed-loop WSAN is guaranteed to be stable are studied. Note that, all works mentioned above on both WSAN and wireless NCS focus on the case of the single controller.…”
Section: Introductionmentioning
confidence: 99%
“…WirelessHART [14], ISA-100 [15]. A significant amount of works have considered WSANs under unreliable wireless communications [16][17][18][19][20][21][22] and real system applications [23,24]. In particular, the problem of optimal controller placement in multi-hop WSANs is addressed in [16,17], and it is shown that placing the controller at the actuator node achieves better performance than at the sensor node under certain conditions.…”
Section: Introductionmentioning
confidence: 99%